Homogenous UV/periodate process in treatment of p-nitrophenol aqueous solutions under mild operating conditions - Saien, Javad (Environmental technology, 2018)
Aqueous solutions of p-nitrophenol (PNP) were treated with UV-activated potassium periodate (UV/KPI) in an efficient photo-reactor. Either periodate or UV alone had little effect; however, their combination led to a significant degradation and mineralization. The response surface methodology was employed for design of experiments and optimization. The optimum conditions for treatment of 30 mg/L of the substrate were determined as [KPI] = 386.3 mg/L, pH = 6.2 and T = 34.6°C, under which 79.5% degradation was achieved after 60 min. Use of 25 and 40 kHz ultrasound waves caused the degradation to enhance to 88.3% and 92.3%, respectively. The intermediates were identified by gas chromatography-mass spectroscopy analysis, leading to propose the reaction pathway. The presence of water conventional bicarbonate, chloride, sulfate and nitrate anions caused unfavorable effects in efficiency. Meanwhile, the kinetic study showed that PNP degradation follows a pseudo-first-order reaction and the activation energy was determined. The irradiation energy consumption required for one order of magnitude degradation was estimated as 11.18 kWh/m3. Accordingly, comparison with the previously reported processes showed the superiority of PNP treatment with the employed process